2016
DOI: 10.1111/cpr.12282
|View full text |Cite
|
Sign up to set email alerts
|

Role of AhR in positive regulation of cell proliferation and survival

Abstract: The aryl hydrocarbon receptor (AhR) is an important nuclear transcription factor that is best known for mediating toxic responses by adjusting numbers of metabolism-related enzymes, including CYP1A1 and CYP1B1. Previous findings have revealed that, in addition to negatively regulating cell proliferation and survival, AhR may also positively regulate these pathways. Here, we review these findings and summarize distinct mechanisms by which AhR promotes cell proliferation and survival, including modulation of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 76 publications
(87 reference statements)
2
49
1
1
Order By: Relevance
“…AHR knockdown inhibits the growth of cancer cells. AHR is highly expressed in a wide panel of tumors and previous studies indicated that overexpression of AHR could help cancer cells survive under cellular stress (34,35). To address whether AHR imparts survival to cancer cells, AHR was knocked down in a variety of cell lines including human ovarian cancer cell line (A2780), human lung cancer cell line (A549), human breast cancer cell line (MDA-MB231), human hepatocellular carcinoma cell line (Bel7402), human colon cancer cell line (HCT-8 and SW620) and human embryonic kidney 293 cells (HEK293).…”
Section: Resultsmentioning
confidence: 99%
“…AHR knockdown inhibits the growth of cancer cells. AHR is highly expressed in a wide panel of tumors and previous studies indicated that overexpression of AHR could help cancer cells survive under cellular stress (34,35). To address whether AHR imparts survival to cancer cells, AHR was knocked down in a variety of cell lines including human ovarian cancer cell line (A2780), human lung cancer cell line (A549), human breast cancer cell line (MDA-MB231), human hepatocellular carcinoma cell line (Bel7402), human colon cancer cell line (HCT-8 and SW620) and human embryonic kidney 293 cells (HEK293).…”
Section: Resultsmentioning
confidence: 99%
“…The AhR is a nuclear transcription factor that mediates toxic responses by adjusting numbers of metabolism-related enzymes, including CYP1A1. The AhR binds to the AhR nuclear translocator (ARNT) and the ligand-bound AhR/ARNT complex translocates from the cytoplasm into the nucleus to modulate the expression of target genes, such as CYP1A1 and CYP1B1 [ 14 ]. IS inhibited the expression of fetuin-A through AhR activation in a human hepatoma HepG2 cell line [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…When ligand bound, conformational changes allow AHR to dissociate from the cytoplasmic complex and bind to a cofactor, aryl hydrocarbon nuclear translocator (ARNT, also called HIF-1B), and together these proteins translocate to the nucleus and bind AHR-response elements in the promoters of target genes [ 4 , 5 ]. While the AHR has many transcriptional targets, the two best characterized are the cytochrome P450 1A1 and 1B1 (CYP1A1 and CYP1B1) genes [ 6 ]. These enzymes belong to the CYP1 family of monoxygenases, and are responsible for the metabolism of a variety of endogenous and xenobiotic molecules into bioactive compounds and toxic derivatives, respectively.…”
Section: Introductionmentioning
confidence: 99%